Day 2 Tue, September 27, 2016 2016
DOI: 10.2118/181516-ms
|View full text |Cite
|
Sign up to set email alerts
|

Why Re-Fracturing Works and Under What Conditions

Abstract: Stimulated shale wells show sharp decline rates after several months of production imposing the need for rejuvenating production via re-fracturing or other methods. The sharp decline in production from shale gas/oil wells is attributed to full or partial closure and damage of the induced fracture network within the rock. The poor economic conditions stirred by low oil prices has persuaded operators to consider re-fracturing as an affordable option but the mechanisms behind this technique is not fully understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Hence, re-fracturing as an emerging technology has become a viable option for sustaining production and increasing reserves. Re-fracturing is a preferred option over drilling and completing new horizontal wells as it can be carried at only a fractional cost of up to 25-40% [37], thus minimizing the related financial and safety risks.…”
Section: Re-fracturing Technologymentioning
confidence: 99%
“…Hence, re-fracturing as an emerging technology has become a viable option for sustaining production and increasing reserves. Re-fracturing is a preferred option over drilling and completing new horizontal wells as it can be carried at only a fractional cost of up to 25-40% [37], thus minimizing the related financial and safety risks.…”
Section: Re-fracturing Technologymentioning
confidence: 99%
“…Field observations of restimulated old wells have revealed that with increasing pumping rates, hydraulic fractures branch out and communicate with microfractures in the reservoir, forming a complex fracture network [17][18][19]. Induced fracture reorientation is very important in the process of refracturing [20].…”
Section: Introductionmentioning
confidence: 99%
“…Shale often accumulates a significant amount of irrecoverable deformation over time. This viscoplastic deformation plays an important role in a variety of subsurface practices, such as in‐situ stress estimation, 1,2 borehole drilling, 3 leakage prevention, 4,5 and hydraulic fracturing 6–8 . This importance has motivated a number of experimental investigations into creep of shale at multiple scales (eg, Refs.…”
Section: Introductionmentioning
confidence: 99%